2022
DOI: 10.3390/toxins14100675
|View full text |Cite
|
Sign up to set email alerts
|

Reasons and Determinants of BoNT-A Treatment Discontinuation in Patients Living with Spasticity: A 10-Year Retrospective Analysis

Abstract: Background: The present study aimed to evaluate the reasons and determinants of BoNT-A discontinuation in patients with stroke, multiple sclerosis, spinal cord injury, and traumatic brain injury. Methods: It is a retrospective study of 56 discontinuer patients treated with botulinum toxin between January 2011 and December 2021. Discontinuation rates and their predictors were estimated using Kaplan–Meier, Log rank test, and Cox’s regression method of analyses.Results: The mean age was 56.54 years, 53.57% were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…In particular, we have included five national guidelines [ 10 , 44 , 45 , 46 , 47 ], two systematic reviews [ 32 , 34 ], a randomized controlled trial [ 43 ], six observational studies [ 22 , 27 , 28 , 35 , 36 , 41 ], three non-systematic reviews [ 33 , 38 , 42 ], a comprehensive overview [ 29 ], consensus report [ 37 ], and three survey-based qualitative studies [ 31 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we have included five national guidelines [ 10 , 44 , 45 , 46 , 47 ], two systematic reviews [ 32 , 34 ], a randomized controlled trial [ 43 ], six observational studies [ 22 , 27 , 28 , 35 , 36 , 41 ], three non-systematic reviews [ 33 , 38 , 42 ], a comprehensive overview [ 29 ], consensus report [ 37 ], and three survey-based qualitative studies [ 31 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study investigated the reasons for BoNT-A treatment discontinuation in subjects affected by spasticity post-stroke as well as other neurological conditions. Regarding stroke, subjects’ logistics reasons and clinical worsening were the most important causes of discontinuation whereas orthopedic surgeries and intrathecal baclofen therapy were frequently a reason for discontinuation for spinal cord injury and traumatic brain injury [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we collected only serious adverse events, while a more in-depth investigation could have led to other statistical associations and, possibly, improved persistence [17]. We did not collect reasons for discontinuation, which can include logistics, switches to other spasticity treatments, poor efficacy, and/or tolerability [18]. However, looking at our results, disease worsening in terms of cognitive impairment and DMT failure are most likely responsible for BT discontinuation.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that it is crucial to identify the possible predictors of discontinuation to improve the efficacy of multidisciplinary management while also confirming the crucial roles of rehabilitation and caregivers in achieving better long-term outcomes [18].…”
mentioning
confidence: 85%